DEVELOPING STUDENTS MACRO LANGUAGE SKILLS INTEGRATEDLY BY INTERCONNECTING THE TARGET CULTURE AND LOCAL WISDOM IN TEFLIN/TEGL/TEIL - Sukarno Sukarno; Saiful Latif (Universitas Khairun, 2023)
The goal of teaching English as a foreign language in Indonesia (TEFLIN), or in a wider context—teaching English as a global language (TEGL) or teaching English as an international language (TEIL), is that the students are able to authentically communicate with others using the target language in real life situations: attending lectures or seminars, having a chat via the Internet, discussing TV programmes, bargaining items in markets, etc. When the communication takes place, the four macro language skills are integratedly employed to convey and receive messages as the contents of communications. This vividly seems that language in use must have contents because language itself merely consists of symbols, grammatical rules in the forms of patterns, and skills. In TEFLIN or TEGL/TEIL, therefore, the teachers/lecturers of English should cater the students with meaningful contents appropriate for them to develop their four macro language skills in meaningful learning atmosphere. The contents encompass the target culture and students' local wisdom related to their real-life situations. The target culture is employed as meaningful input texts for receptive skills: listening and reading. The input texts are then employed to explore and elaborate on local wisdom related to the target culture for productive skills: writing and speaking. The steps proposed are as follows: 1) warming the students up with relevant situation to the topic, 2) presenting input texts about the target culture to discuss (listening or reading), 3) analysing the ways of expressing ideas used in the target language—English, 4) analysing and discussing the language elements, and 5) employing the learned ways of expressing ideas in productive skills (writing and speaking) about local wisdom related to students’ real-life situations in the target language.